Putin's kleptocracy : who owns Russia? - Dawisha, Karen (Simon & Schuster, 2014)
The raging question in the world today is who is the real Vladimir Putin and what are his intentions. Karen Dawisha's brilliant work provides an answer, describing how Putin got to power, the cabal he brought with him, the billions they have looted, and his plan to restore the Greater Russia.